2011
DOI: 10.1158/0008-5472.can-10-3795
|View full text |Cite
|
Sign up to set email alerts
|

p95HER2 and Breast Cancer

Abstract: A subtype of HER2-positive tumors with distinct biological and clinical features expresses a series of carboxyterminal fragments collectively known as p95HER2. One of these fragments, named 100-to 115-kDa p95HER2 or 611-CTF, is hyperactive because of its ability to form homodimers maintained by intermolecular disulfide bonds. Despite lacking the majority of the extracellular domain, this HER2 fragment drives breast cancer progression in vivo. The recent availability of specific anti-p95 antibodies has confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
163
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(167 citation statements)
references
References 29 publications
0
163
0
4
Order By: Relevance
“…ErbB-2 is a major therapeutic target in breast cancer and the therapeutic agent used is an antibody to the ectodomain. Therefore the presence of these biologically active CTFs in tumor tissue represents a potential therapeutic problem (Arribas et al 2011). …”
Section: Nuclear Rtksmentioning
confidence: 99%
“…ErbB-2 is a major therapeutic target in breast cancer and the therapeutic agent used is an antibody to the ectodomain. Therefore the presence of these biologically active CTFs in tumor tissue represents a potential therapeutic problem (Arribas et al 2011). …”
Section: Nuclear Rtksmentioning
confidence: 99%
“…EGFR and Erb-B2 activation may also be involved with resistance to radiotherapy, since both are upregulated/activated following exposure to ionising radiation. targeted therapies have been described, including subversion of trastuzumab binding to Erb-B2 by shed p95 ECD fragments (Ar- (Arribas et al, 2011); a switch to alternative signaling via other Erb-B family members (notably Erb-B3), alternative RTK such as c-MET, -ments (e.g. PI3 kinase-AKT-FOX1A) for example via loss of PTEN or by PIK3CA mutations.…”
Section: Links Between Erb-b Signalling and Resistance To Therapymentioning
confidence: 99%
“…Trastuzumab (Herceptin, Genentech, South San Francisco, CA, USA), a humanised MAB directed against the extracellular domain of HER2 (Carter et al 1992), has been shown to selectively exert anti-tumour effects in cancer models and patients with HER2-enriched breast cancer (Vogel et al 2002, Romond et al 2005. Despite the clinical effectiveness of trastuzumab in the treatment of HER2C tumours, intrinsic or secondary resistance to trastuzumab represents a significant hurdle (Arribas et al 2011), highlighting the importance of developing new therapies for this disease.…”
Section: Introductionmentioning
confidence: 99%